The Perplexing Bilateral Relations between Two Koreas: Finding Peace in Korean Reunification Through Critical Theory's Perspective - Rahmawati, Dea (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2023)
Despite being formerly homogeneous in terms of history, culture, language, and nation, the separation of the Korean people has led to significant contrasts in political, economic, and cultural aspects between South Korea and North Korea. Conflict resulting from these differences eventually leads to war. However, since World War II, the two Koreas have been seeking reunification in three different ways: